The (in)visibility of Colonial Wars in Mia Couto and J. M. Coetzee - Vieira, Patrícia (2012)
Colonialism is grounded in a play of appearances, where colonizers dictate the way to interpret phenomena and the very mode of their unveiling so as to justify their position. Thus, blatant socio-economic imbalances are recoded as the white man’s burden to civilize others. Outward impressions such as skin colour, dress codes or a particular accent determine an individual’s place in the strictly hierarchic colonial edifice, where stereotypes and racism are naturalized and described as a response to the attributes of the colonized. J. M. Coetzee’s novel Waiting for the Barbarians (1980) and Mia Couto’s novella Vinte e Zinco (1999) foreground the central role of appearances in the ideological construction of colonial empires. Both texts focus on pivotal moments in the colonial societies they depict, since the narration takes place at a time of war and social conflict. Coetzee portrays an unidentified empire that has recently seen an increase in attacks by so-called barbarians, whose threat, real or imaginary, leads the state into the cruellest atrocities. Mia Couto’s narrative, as with several other texts by the author,¹ also concentrates on a period of transition in Mozambique’s recent past. The book describes events taking place in the small village of Moebase between 19th and 30th April, 1974, a time when the colonial system is collapsing. The two tales thus dwell on periods of rapid change, when the elusive laws that determine what is apparent and inapparent in the colonial context are in the process of being rewritten. This shift allows for a re-evaluation of what the colonizers had hitherto defined as obvious but also foreshadows the political upheavals of the post-colonial period, when many of the colonial structures of power are kept in place.